The methodology of control over preparedness of elite swimmers based on relationship between the power of active metabolism, mechanical power and efficiency and swimming velocity - Kolmogorov, S. V.; Vorontsov, A. R. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The model for description of swimming performance unifying metabolic and biomechanical criteria (power and efficiency) was practically verified during the preparation of the Russian National Team for the World Short Course Swimming Championships 2014. Our study investigated elite swimmers - members of the Russian National Swimming Team. The athletes performed in a 25-m pool 4 times (once within every training block) a swimming test with a step-like increase of swimming velocity (intensity): sprinters - 8 x 100 m, middle distance swimmers - 8 x 200 m. The parameters of gas exchange, including VO2, VE, RER were determined after each stage of the test using "MetaMax" mobile system. Blood samples were taken from earlobes and examined for peak lactate concentration after each stage using a "GL easy" analyzer. VO2 and Lactate data were used to determine the total metabolic power. The frontal components of hydrodynamic resistance, mechanical power and efficiency were estimated using the small perturbation method (Kolmogorov-Duplisheva, 1992). The dynamics of individual metabolic and mechanical power and efficiency characteristics and their ratio were studied and compared against the outcome of training programs. We recommend the using the studied characteristics for planning and correction of individual training programs.